Arkitektura a documentary on the Spanish influence on Philippine architecture - Cultural Center of the Philippines; Jose, Regalado Trota; Perez, Rodrigo D. (Manila The Center, 1992)
The Spanish colonial regime introduced architectural concepts and techniques which were adapted to native needs and traditions to produce buildings that are now part of Filipino cultural identity, such as the bahay kubo, the bahay na bato, the cathedral and the visita.
Narration, Luis Guerrero Nakpil ; producers, Rowena E. Concepcion, Mary Ann Ines-Loveria.
VHS.
Keywords: Architecture -- Philippines; Architecture, Spanish colonial -- Philippines